1980
DOI: 10.1351/pac198052051323
|View full text |Cite
|
Sign up to set email alerts
|

Research on enhanced oil recovery: past, present and future

Abstract: -Past and present research on Enhanced Oil Recovery is reviewed with emphasis on the surfacephenomena involved. The nature of capillary pressure phenomena in porous media has been understood for some time, and much research has been devoted towards the alteration of the surface forces which prevent the efficient displacement of oil by water .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 85 publications
1
47
0
Order By: Relevance
“…It is important to note that capillary trapping has been shown to be a dominant mechanism for oil trapping in depleted oil fields. It has been found that, even following secondary recovery processes, more than 50% of the original oil remains trapped as a discontinuous phase [95,96].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that capillary trapping has been shown to be a dominant mechanism for oil trapping in depleted oil fields. It has been found that, even following secondary recovery processes, more than 50% of the original oil remains trapped as a discontinuous phase [95,96].…”
Section: Introductionmentioning
confidence: 99%
“…The residual saturation of a displacement phase is related with viscous forces, surface forces (interfacial tension) and capillary number [10]. The capillary number [7], N cn , is defined as a dimensionless ratio of viscous to local capillary forces(equation 5).…”
Section: Theoretical Discussion For Eormentioning
confidence: 99%
“…However, several definitions are possible as long as they are relevant and consistent [11][12][13][14]; in SARIP CH , we chose N c = (R m μ w u w + μ o u o )/σ ow where R m is the polymer mobility reduction.…”
Section: Saripmentioning
confidence: 99%